Aktivitas Antagonis Bacillus subtilis terhadap Streptococcus iniae dan Pseudomonas fluorescens (ANTAGONIST ACTIVITY OF BACILLUS SUBTILIS AGAINST STREPTOCOCCUS INIAE AND PSEUDOMONAS FLUORESCENS) - Budianto, Budianto; Suprastyani, Heny (Jurnal Veteriner; Vol 18 No 3 (2017)DO - 10.19087/jveteriner.2017.18.3.409, 2017)
Intensification of fish farming has caused various impacts, for example diseases in fish. One of the diseases in fish is a bacterial disease. The use of probiotic bacteria as an antimicrobial agent, which is relatively safe and effective, is a strategy to treat the disease. Bacillus subtilis is probiotic bacteria which can produce bacteriocin compounds and has antagonistic effects against both Gram negative and Gram positive bacteria. The aim of this study was to evaluate the antagonist activity of B. subtilis against Streptococcus iniae and Pseudomonas fluorescens . Antagonist activity test was done by using paper disc diffusion against the bacteria. The variations on the test paper disc method used were based on the difference of B. subtilis incubation time, such as: 0, 6, 12, 18, 24 and 30 hours. The results showed B. subtilis (generation time = 30.62 min) produced antibacterial compounds which inhibited the growth of the bacteria. Antagonist activity was detected in early exponential phase, six hours, with inhibition zone diameter of 7.28 ± 0.18 mm ( S. iniae ) and 6.75 ± 0.11 mm ( P. fluorescens ) and reached optimum at early stationary phase, 24 hours, the inhibition zone diameter of 8.84 ± 0.28 mm ( S. iniae ) and 9.14 ± 0.91 mm ( P. fluorescens ). It can be concluded that B. subtilis can contribute in controlling the spread of bacterial diseases in fish farming, particularly caused by S. iniae and P. fluorescens ABSTRAK Intensifikasi budidaya ikan telah menyebabkan berbagai dampak, seperti penyakit pada ikan. Salah satunya adalah penyakit bakteriawi. Penggunaan bakteri probiotik sebagai agen antimikrob yang aman dan efektif adalah salah satu strategi untuk menanggulangi penyakit tersebut. Bacillus subtilis merupakan bakteri probiotik yang dapat memproduksi senyawa bakteriosin dan memiliki efek antagonis terhadap bakteri Gram negatif dan positif. Tujuan dari penelitian ini adalah untuk mengevaluasi aktivitas antagonis dari B. subtilis terhadap Streptococcus iniae dan Pseudomonas fluorescens. Uji aktivitas antagonis dilakukan dengan menggunakan difusi cakram kertas terhadap bakteri uji. Variasi perlakuan pada uji cakram kertas adalah menggunakan perbedaan waktu inkubasi B. subtilis , yaitu waktu inkubasi 0, 6, 12, 18, 24 dan 30 jam. Berdasarkan hasil penelitian, B. subtilis (waktu generasi=30,62 menit) dapat memproduksi senyawa antibakteri yang dapat menghambat pertumbuhan bakteri uji. Aktivitas antagonis terdeteksi pada awal fase eksponensial yaitu inkubasi enam jam, dengan diameter zona hambat sebesar 7,28 ± 0,18 mm ( S. iniae ) dan 6,75 ± 0,11 mm ( P. fluorescens ) dan mencapai optimum pada awal fase stasioner yaitu inkubasi 24 jam, dengan diameter zona hambat sebesar 8,84 ± 0,28 mm ( S. iniae ) dan 9,14 ± 0,91 mm ( P. fluorescens ). Dapat disimpulkan bahwa B. subtilis dapat berperan dalam pengendalian penyebaran penyakit bakteri pada budidaya ikan, khususnya yang disebabkan oleh S. iniae dan P. fluorescens .